Postpartum Anxiety, Breastfeeding Self-Efficacy & Breastfeeding Outcomes. (29th May 2020) - Klenzman, Rachel; Spence, Marsha; Colby, Sarah; Springer, Cary; Kavanagh, Katie
Abstract: Objectives: Postpartum anxiety is associated with failure to meet breastfeeding (BF) goals. While BF self-efficacy is a potential moderator of this relationship, the relationship between postpartum anxiety, BF self-efficacy, and exclusive breastfeeding (EBF) has not yet been assessed. The objective was to assess relationships between EBF, anxiety, depression, and BF self-efficacy scores. Methods: An online survey using the State-Trait Anxiety Inventory (STAI), Edinburgh Postnatal Depression Scale (EPDS), and Breastfeeding Self-Efficacy Scale (BSES) was conducted. Eligible mothers were ³ 18 years old, had infants 4–24 weeks old, and had provided breastmilk in the prior 2 weeks. Screening stratified by anxiety across 4 groups (no, low, moderate, high) using the Generalized Anxiety Disorder-7 (GAD) tool to ensure sample variability. Possible score ranges for each scale were: GAD (0–21), STAI (20–80), EPDS (0–30), and BSES (14–70). Full sample correlations assessed relationships between STAI, EPDS, and BSES scores. Independent t-tests assessed for differences in scale scores by EBF status. Results: Participants ( n = 129) were primarily white (92.2%), non-Hispanic (90.7%), married (74.4%), and primiparous (62%). About half were low income and 56.6% reported EBF. Mean scale scores were as follows: GAD = 8.2 (+5.7); STAI = 24.6 (+12.9); EPDS = 9.7 (+4.6); and BSES = 56.8 (+11.4). STAI and EPDS scores were positively correlated ( P < .001). BSES scores negatively correlated with STAI ( P = .027) and EPDS ( P < .001) scores. BSES scores were higher among those reporting EBF (60.0 vs. 53.3; P < .001). Conclusions: In this sample of mostly white, non-Hispanic, married women, preliminary findings indicate potentially important relationships between BF self-efficacy and anxiety and depression, and suggest these relationships may impact EBF. Future work, increasing our understanding of the relationship between postpartum anxiety and EBF, may provide important intervention pathways. Funding Sources: There was no funding source for this project.